2019
DOI: 10.3390/en12214034
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of a Biogas-Based Power Plant from Organic Waste in the North Netherlands

Abstract: Biogas is expected to play a crucial role in achieving the energy targets set by the European Union. Biogas, which mainly comprises methane and carbon dioxide, is produced in an anaerobic reactor, which transforms biomass into biogas. A consortium of anaerobic bacteria and archaea produces biogas during the anaerobic digestion (AD) of various types of feedstocks, such as animal slurries, energy crops, and agricultural residues. A biogas-fed gas turbine-generator and steam generator produce heat and power. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The awareness of the trade-offs and limitations in terms of the biogas feedstocks and the consequences on the nutrient cycling (especially nitrogen recycling capacity) should be taken into account when making decisions related to anaerobic digestion (Hoang et al, 2020). To address this, a recent study in the Netherlands showed that net present value (a feasibility indicator) of biogas plants treating cow manure and sugar beet pulp was negative to an extent that the subsidy was not sufficient to make it feasible while switching to straw combined with cattle manure promoted the cost effectiveness (Achinas et al, 2019). Overall, high investment and operating costs limit feasibility of anaerobic digestion and therefore subsidy plays a great role in the profitability of this technique (Gebrezgabher et al, 2012).…”
Section: Anaerobic Manure Digestionmentioning
confidence: 99%
“…The awareness of the trade-offs and limitations in terms of the biogas feedstocks and the consequences on the nutrient cycling (especially nitrogen recycling capacity) should be taken into account when making decisions related to anaerobic digestion (Hoang et al, 2020). To address this, a recent study in the Netherlands showed that net present value (a feasibility indicator) of biogas plants treating cow manure and sugar beet pulp was negative to an extent that the subsidy was not sufficient to make it feasible while switching to straw combined with cattle manure promoted the cost effectiveness (Achinas et al, 2019). Overall, high investment and operating costs limit feasibility of anaerobic digestion and therefore subsidy plays a great role in the profitability of this technique (Gebrezgabher et al, 2012).…”
Section: Anaerobic Manure Digestionmentioning
confidence: 99%
“…Solid and semi-solid entry materials are mixed with the liquid suspension in order for us to get the homogenous suspension. At the same time, rough particles and fibrous matter are cut [10][11].…”
Section: The Combination Of Premix With Rotacut Pumpmentioning
confidence: 99%
“…The awareness of the trade-offs and limitations in terms of the biogas feedstocks and the consequences on the nutrient cycling (especially nitrogen recycling capacity) should be taken into account when making decisions related to anaerobic digestion (Hoang et al 2020). To address this, a recent study in the Netherlands showed that net present value (a feasibility indicator) of biogas plants treating cow manure and sugar beet pulp was negative to an extent that the subsidy was not sufficient to make it feasible while switching to anaerobic digestion with cattle manure combined with straw increased the cost effectiveness (Achinas et al 2019). Overall, high investment and operating costs limit feasibility of anaerobic digestion and therefore subsidy plays a great role in the profitability of this technique (Gebrezgabher et al 2012).…”
Section: Medium -Highmentioning
confidence: 99%